2021
DOI: 10.3168/jds.2020-18926
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cheese-processing conditions and curd and cheese properties to improve the yield of Idiazabal cheese made in small artisan dairies: A multivariate approach

Abstract: Very diverse cutting and cooking intensity processes are currently used in small artisan dairies to manufacture Idiazabal cheese. The combination of the technical settings used during cheese manufacturing is known to affect cheese composition and yield, as well as whey losses. However, the information regarding the effect on microstructure and texture of cheese is scarce, especially in commercial productions. Therefore, the effect of moderate-and high-intensity cutting and cooking processes on whey losses, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…After 240 days of ripening, batch L4 had the highest fat content (54.4 AE 1.50), while batch L2 had the lowest (52.7 AE 1.5). The evolution of the fat and protein content of the cheeses included in this study followed a similar trend to that observed in other studies (Mezo-Sol ıs et al 2020; Aldalur et al 2021), although the contents in the present study were slightly higher.…”
Section: Changes In Chemical and Physicochemical Parameters During Ri...supporting
confidence: 91%
“…After 240 days of ripening, batch L4 had the highest fat content (54.4 AE 1.50), while batch L2 had the lowest (52.7 AE 1.5). The evolution of the fat and protein content of the cheeses included in this study followed a similar trend to that observed in other studies (Mezo-Sol ıs et al 2020; Aldalur et al 2021), although the contents in the present study were slightly higher.…”
Section: Changes In Chemical and Physicochemical Parameters During Ri...supporting
confidence: 91%
“…This differentiation could be due to several reasons, such as differences in milk composition [ 73 , 74 ] or different cheese-making and ripening conditions [ 54 , 70 ]. For instance, Aldalur et al [ 75 ] have reported differences in cooking pH and whey-draining pH between Idiazabal cheese producers. The type of rennet used or the concentration of coagulant enzyme employed have also been described as affecting the gross composition of cheese, including pH or protein content [ 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, producers may employ different flock management and cheese making practices that, in turn, affect the quality of the milk and final cheese. The most notable differences are related to the flock management and grazing practices, such as valley or mountain grazing ( Abilleira et al, 2010a ; Valdivielso et al, 2016 ); the use of artisanal or commercial rennet ( Virto et al, 2003 ) or the technological conditions used for cheese making and ripening ( Aldalur et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%